(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
We herein report a case of a 23-year-old woman suffering from pica who committed suicide by hanging from ceiling fan in her room. She was apparently healthy and had not diagnosed of any medical or psychiatric disorder except that nearly 7 years ago her family noticed that she was into the habit of consuming soil, pencils and chalks. Often she would be confronted by her family members because of pica which would subsequently leave her deeply distressed. A day before the suicide, after one such argument she appeared to be unusually upset. She had left a suicide note which revealed inability to understand her problems by the family members. In this paper, we also discuss the psycho-social aspects associated with pica and highlight some of the potential complications that can result from it.